![Ex 4.1, 3 - Chapter 4 Class 11 Mathematical Induction - Part 2](https://cdn.teachoo.com/f23b371c-ebee-49b3-9fb0-96c3b1a924c8slide22.jpg)
![Ex 4.1, 3 - Chapter 4 Class 11 Mathematical Induction - Part 3](https://cdn.teachoo.com/d59ce406-6480-435a-aa30-dbdf8903ac01slide23.jpg)
![Ex 4.1, 3 - Chapter 4 Class 11 Mathematical Induction - Part 4](https://cdn.teachoo.com/9a5e67ee-3612-434c-bbb4-9c7f3595f93eslide24.jpg)
Equal - 1 upon addition
Last updated at Dec. 16, 2024 by Teachoo
Question3: Prove the following by using the principle of mathematical induction for all n N: 1 + 1/((1 + 2)) + 1/((1 + 2 + 3)) + .. + 1/((1 + 2 + 3 + . )) = 2 /(( + 1)) Let P (n) : 1 + 1/((1 + 2)) + 1/((1 + 2 + 3)) + .. + 1/((1 + 2 + 3 + . )) = 2 /(( + 1)) For n = 1, L.H.S = 1 R.H.S = 2(1)/(((1) +1)) = 2/((2)) = 1 Hence, L.H.S. = R.H.S , P(n) is true for n = 1 Assume P(k) is true 1 + 1/((1 + 2)) + 1/((1 + 2 + 3)) + .. + 1/((1 + 2 + 3 + + )) = 2 /(( + 1)) We will prove that P(k + 1) is true. R.H.S = 2( + 1)/((( + 1) + 1) ) L.H.S = 1 + 1/((1 + 2)) + 1/((1 + 2 + 3)) + .. + 1/((1 + 2 + 3 + +( + 1)))